2023
DOI: 10.1161/jaha.123.029428
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Exposure to Ambient PM 2.5 and Hospitalizations for Myocardial Infarction Among US Residents: A Difference‐in‐Differences Analysis

Yichen Wang,
Xinye Qiu,
Yaguang Wei
et al.

Abstract: Background Air pollution has been recognized as an untraditional risk factor for myocardial infarction (MI). However, the MI risk attributable to long‐term exposure to fine particulate matter ≤2.5 μm in aerodynamic diameter (PM 2.5 ) is unclear, especially in younger populations, and few studies have represented the general population or had power to examine comorbidities. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Similarly, Brunekreef et al 15 observed steeper slopes at low exposures to PM 2.5 below 15 µg/m 3 and NO 2 below 40 µg/m 3 in the supralinear associations for stroke incidence, based on data from 22 European cohorts in the European Study of Cohorts for Air Pollution Effects Project. Several previous studies of the Medicare population have found a greater risk of a range of cardiovascular outcomes when restricted to lower exposures 9,13,14,27 . Our main nding adds to epidemiologic evidence of potential population-level health concerns at pollution levels conventionally considered safe and provides some assurance that the associations are not biased by unmeasured confounding.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Brunekreef et al 15 observed steeper slopes at low exposures to PM 2.5 below 15 µg/m 3 and NO 2 below 40 µg/m 3 in the supralinear associations for stroke incidence, based on data from 22 European cohorts in the European Study of Cohorts for Air Pollution Effects Project. Several previous studies of the Medicare population have found a greater risk of a range of cardiovascular outcomes when restricted to lower exposures 9,13,14,27 . Our main nding adds to epidemiologic evidence of potential population-level health concerns at pollution levels conventionally considered safe and provides some assurance that the associations are not biased by unmeasured confounding.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies found the shape of the exposure-response curves for long-term PM 2.5 and all-cause and cardiovascular mortality to be curvilinear with no evidence of a threshold 11,12 . According to several studies of large cohorts in the US 9,13,14 and Europe 15,16 , the risk of cardiovascular diseases could persist and even become stronger at lower exposure levels below the annual limit values set by the US Environmental Protection Agency (EPA) and European Union (EU). The suggested higher incremental risk in relation to a lower air pollutant level raises the question of whether the national and international air quality guidelines are protective enough.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollutants are composed of particulate matter (PM), including coarse particles, characterized by being 10 micrometers or less to 2.5 micrones in size (PM10); fine particles, defined as being 2.5 micrones or less in diameter (PM2.5); and ultrafine particles and gaseous pollutants, such as nitrogen dioxide and ozone. The inhalation of PM2.5 generated by the combustion of fossil fuels is considered as one of the non-traditional risk factors for coronary artery disease [1].…”
Section: Introductionmentioning
confidence: 99%